Psmd13, a proteasome regulatory subunit identified in miR-29a regulation during neuronal differentiation - Diji Kuriakose; Grant Morahan; Zhi-cheng Xiao (PLoS ONE, 2026)
miR-29a is essential for neuronal development and implicated in neurodegenerative disease, yet its upstream regulation remains unclear. Using genetically diverse Collaborative Cross (CC) mice, we performed expression profiling and QTL mapping, identifying a strong locus on chromosome 7. Among ten candidates, Psmd13 emerged as a key regulator. RNAi-mediated Psmd13 knockdown in mouse neural precursor cells (mNPCs) enhanced neuronal differentiation, with miR-29a upregulated in the undifferentiated state but reduced upon differentiation. Co-immunoprecipitation suggested an association between Psmd13 and Dicer, correlating with state-dependent changes in miR-29a levels. ChIP-seq revealed overlapping chromatin occupancy of Psmd13 and Dicer at several genomic loci, including miR-29a, consistent with—but not directly demonstrating—a role in chromatin accessibility and transcriptional control. Proteasome inhibition with MG132 lowered Psmd13 and Dicer, suppressed miR-29a, and impaired neuronal differentiation. Together, these findings suggest that differentiation dynamically regulates miR-29a expression through Psmd13–Dicer interactions, supporting a model in which Psmd13 acts as an upstream modulator of miRNA control and neurodevelopmental homeostasis.